Adverse childhood experiences and MSM marijuana use. (1st May 2019) - Giano, Zachary; Hubach, Randolph D.; Currin, Joseph M.; Wheeler, Denna L.
Highlights: No significant differences between rural and urban MSM ACEs. Urban MSM had significantly higher self-reported marijuana use than rural MSM. ACEs predicted reported marijuana use in urban, but not rural MSM. Abstract: Background: Past research identified individuals who experienced adverse childhood experiences (ACEs) are at a higher risk of drug use. There is evidence to suggest that identifying as a man who has sex with other men (MSM) may increase the likelihood of drug use when adverse childhood experiences are prevalent. However, research has not addressed if this association is present in both rural and urban MSM, as other studies found that rurality/urbanity is a key determinant in detrimental outcomes for MSM. The current study uses ACEs as an independent variable in comparing rural and urban MSM's self-reported marijuana use. Methods: Participants included 156 MSM residing in Oklahoma. Linear regression was used to test ACEs' associations with reported marijuana use. To explore nuanced differences between rural and urban populations, split sample regressions were conducted. Results: ACEs were statistically associated with reported marijuana use in the full sample. However, after splitting the sample, ACEs only predicted reported marijuana use in the urban and not in the rural sample. Conclusions: Results suggest ACEs may affect rural and urban MSM dissimilarly. It is unclear, however, if rural MSM engage in maladaptive behaviors other than marijuana use, or if factors associated with urban environments make urban MSM more vulnerable to illicit drug use when ACEs are high. Regardless, trauma informed programming targeting MSM should consider geographic locale as an influential factor. Further investigation is needed with regards to geographic locale, ACEs, and other illicit drug use in MSM populations.